Reexamining the relationship between inventory management and firm performance: An organizational life cycle perspective - Khaled Elsayed; Hayam Wahba (Future Business Journal, 2016)
Existing evidence regarding inventory-performance relationship is inconclusive. A perspective that this paper stresses in considering this relationship is that it might depend on organizational life cycle stage. The underlying assumptions of this argument are that organization's strategies and relationships vary with its life cycle stage, organizations develop their own strategies to fit between inventory system and organizational settings, and design of inventory system is not a linear process, rather it is a dynamic process that emerges and evolves in response to the power and interests of the stakeholders. Econometric analysis provides support for this argument. Specifically, the results show that while inventory to sales ratio affects organization performance negatively in the initial growth stage and the maturity stage, it exerts a positive and significant coefficient on performance in either the rapid growth stage or the revival stage. An implication of these findings is that existing perspectives might need to be treated as complementary viewpoints, each of which comprises a part of the whole picture because depending on just one single perspective is likely to result in misleading conclusions about the whole structure.
Keywords: 650; Firm performance; Inventory management; Organizational life cycle; Panel data